High-Throughput Screening and Identification of Human Adenovirus Type 5 Inhibitors - Wen, Xiaojing; Zhang, Li; Zhao, Shan; Liu, Qiang; Guan, Wenyi; Wu, Jiajing; Zhang, Qiwei; Wen, Hongling; Huang, Weijin (Frontiers in Cellular and Infection Microbiology, 2021)
Human adenovirus infections can develop into diffuse multi-organ diseases in young children and immunocompromised patients, and severe cases can lead to death. However, there are no approved antiviral drugs available to treat adenovirus diseases. In this study, a chemiluminescence-based, high-throughput screening (HTS) assay was developed and applied to screen human adenovirus 5（HAdV5）inhibitors from 1,813 approved drug library and 556 traditional Chinese medicine-sourced small-molecule compounds. We identified three compounds with in vitro anti-HAdV5 activities in the low-micromolar range (EC50 values 1.2-4.5 μM, selectivity index values 20-75) that also showed inhibitory effects on HAdV3. Cardamomin (CDM) had good anti-HAdV5 activity in vitro. Furthermore, three dilutions of CDM (150, 75, and 37.5 mg/kg/d) administered to Balb/c mouse models inhibited HAdV5-fluc infection at 1 day post-infection by 80% (p < 0.05), 76% (p < 0.05), and 58% (p < 0.05), respectively. HE-staining of pathological tissue sections of mice infected with a wildtype adenoviral strain showed that CDM had a protective effect on tissues, especially in the liver, and greatly inhibited virus-induced necrosis of liver tissue. Thus, CDM inhibits adenovirus replication in vivo and in vitro. This study established a high-throughput screening method for anti-HAdV5 drugs and demonstrated CDM to be a candidate for HAdV5 therapy, potentially providing a new treatment for patients infected with adenoviruses.